Accountability and Exit Exams in Higher Education: A Systematic Literature Review - Teshome, Samson Worku (Lembaga Yasin AlSys, 2025)
Exit exams have become a significant tool in assessing student competency and ensuring accountability in educational systems worldwide. This systematic literature review aims to explore the relationship between exit exams and accountability in higher education, focusing on their impact on educational quality, student outcomes, and institutional performance. Utilizing the PRISMA framework and the PICO strategy, the researcher conducted a comprehensive search of relevant studies published between 1999 and 2024. The review synthesizes findings from 34 studies, highlighting the role of exit exams in enhancing accountability, the challenges associated with their implementation, and their effects on students and institutions. The results indicate that while exit exams can improve educational standards and accountability, they also pose significant challenges, including increased stress for students and potential inequities. The discussion emphasizes the need for balanced policies that consider both the benefits and drawbacks of exit exams. This review contributes to the ongoing debate regarding the role of exit exams in higher education and provides recommendations for policymakers and educators.